1998
DOI: 10.1076/opge.19.2.81.2324
|View full text |Cite
|
Sign up to set email alerts
|

Ophthalmic manifestations of trisomy 8 mosaic syndrome

Abstract: Trisomy 8 mosaicism can present with a varied clinical picture. A significant number of cases have ocular manifestations. The most commonly reported in the literature have been corneal abnormalities and strabismus. We present a case of trisomy 8 mosaic syndrome with very different ophthalmic manifestations, some of which are previously unreported in the literature. The patient who was known to have trisomy 8 mosaic syndrome was referred with concerns about his visual abilities. He had a characteristic facial d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 5 publications
2
20
0
Order By: Relevance
“…[5][6][7][8] Neurologic abnormalities observed in our patient have also been described in other ADA-deficient patients. 9,10 Although busulfan administration precipitated the onset of cytopenia, the underlying T8M might have played a role in the lack of marrow function recovery from the transduced CD34 ϩ cells or from the untransduced back-up marrow.…”
Section: Resultssupporting
confidence: 51%
“…[5][6][7][8] Neurologic abnormalities observed in our patient have also been described in other ADA-deficient patients. 9,10 Although busulfan administration precipitated the onset of cytopenia, the underlying T8M might have played a role in the lack of marrow function recovery from the transduced CD34 ϩ cells or from the untransduced back-up marrow.…”
Section: Resultssupporting
confidence: 51%
“…1 In addition to strabismus, there have been reports of optic atrophy, chronic uveitis, hypertelorism, blepharophimosis, microphthalmia, ptosis, heterochromia, cataract, bilateral Duane syndrome, congenital pendular nystagmus, abnormal ERG with decreased cone function, and foveal hypoplasia. 2,3 One histopathological evaluation of a characteristic corneal opacity found a richly vascularized yellowwhite fibrous tissue in the anterior stroma. 4 A more recent histopathologic study revealed mature adipose tissue; 92% of these cells were trisomic for chromosome 8 by cytogenetics.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 The most common is strabismus, found in more than 50% of patients; there have also been at least 5 reports of a creamy stromal corneal opacity. 3 To our knowledge, on the basis of a MEDLINE search performed in December 2004 using the terms trisomy 8 mosaicism, retinitis pigmentosa, Leber congenital amaurosis, and retinal dystrophy, this is the first report of a congenital retinal dystrophy with an extinguished electroretinogram (ERG) in association with this syndrome, as well as the first report of spontaneous improvement of a characteristic corneal opacity.…”
mentioning
confidence: 99%
“…The skeletal profile is so characteristic that the diagnosis can be made from chest radiograph (Beighton et al, 1999). CT8M has multiple ophthalmic manifestations, which were reviewed by Anwar et al (1998), who also reported a new patient with Duane's syndrome. Thus, our patient represents the second report of Duane's syndrome in CT8M.…”
Section: Discussionmentioning
confidence: 98%